Business objectives : - Hollett, Vicki (Oxford University Press, 2006)
This completely updated edition of Business Objectives contains an interactive CD-ROM. The course develops the skills students need to participate in a variety of business contexts. It offers controlled grammar practice, systematic teaching of relevant vocabulary, and challenging activities that encourage students to use their own business experience.